2018
DOI: 10.1111/eci.12927
|View full text |Cite
|
Sign up to set email alerts
|

Clock genes alterations and endocrine disorders

Abstract: Clock genes are associated with various endocrine disorders through complex mechanisms. However, data on humans are scarce. Moreover, clock genes exhibit a tissue-specific expression representing an additional level of regulation. Their specific role in endocrine disorders and their potential implications remain to be further clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 129 publications
(323 reference statements)
0
47
0
Order By: Relevance
“…During the past several decades, an understanding of the circadian clock and metabolism has made significant advances. Moreover, environments that include cycles of rest and activity, feeding/fasting times and social stressors, have tremendous impacts on human physiology and metabolism (Angelousi et al, 2018). NAFLD, which is recognized as a lipid metabolic disease is closely connected with the circadian clock.…”
Section: Resultsmentioning
confidence: 99%
“…During the past several decades, an understanding of the circadian clock and metabolism has made significant advances. Moreover, environments that include cycles of rest and activity, feeding/fasting times and social stressors, have tremendous impacts on human physiology and metabolism (Angelousi et al, 2018). NAFLD, which is recognized as a lipid metabolic disease is closely connected with the circadian clock.…”
Section: Resultsmentioning
confidence: 99%
“…As other nuclear receptors, they also have nongenomic effects such as angiogenesis, microfilament cytoplasmic architecture, cellular respiration [15] and the immune reaction [16]. Thyroid receptors expression shows circadian variation in hepatocytes and adipose tissue in mice [17] and the interruption of this physiological rhythm is another possible mechanism to be considered when analysing the effect of sleep short duration and or misalignment. Some other experimental data supports that hypo and hyperthyroidism affect the clock genes tissue expression; for example, an experimental study showed a significant effect on myocardial metabolism related to the circadian rhythm [18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the dark phase, CRY and PER expression decrease to the CRY-PER repressor complex. This leads to a new cycle of the transcription activation of the CLOCK-BMAL1 complex, which completes the basic auto regulatory loop (8, 13). Otherwise, different modulators display fine tuning of output signals in molecular clock.…”
Section: Circadian Clock Mechanism Clock Genes and Cancermentioning
confidence: 99%
“…Changes in circadian clock increase risk of different cancers in endocrine tissues which require daily proliferation to carry out their activity. Thus, a considerable part of endocrine signals are clock-controlled (8). The dysregulation mechanisms of the circadian clock genes is greatly affected by polymorphic variants of circadian clock-related genes, which can raise human cancer risk through different physiological systems (9).…”
Section: Introductionmentioning
confidence: 99%